2021
DOI: 10.3390/ani11113220
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Treating Hatching Eggs with Curcumin after Exposure to Thermal Stress on Embryonic Development, Hatchability, Physiological Body Reactions, and Hormonal Profiles of Dokki-4 Chickens

Abstract: This study evaluated the impact of incubation temperature and spraying hatching eggs with curcumin during the early embryogenesis phase on chick embryo developments, hatchability, physiological body reactions, and hormonal profiles of Dokki 4 chickens. A total of 720 fertile eggs were equally distributed into two groups. In the first group, the eggs were incubated at normal incubation temperature/NIT (37.8 °C and 55–60% RH) for up to 19 days of incubation, whereas those in the second group were incubated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
2
2
0
Order By: Relevance
“…However, the higher plasma triiodothyronine recorded in the birds fed Curcuma longa in this present study depicts a better thermotolerance by the birds, suggesting the beneficial effect of the bioactive compounds of Curcuma longa . Consistent with our result [ 75 ], demonstrated chicks from hatching eggs sprayed with curcumin had higher plasma triiodothyronine.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the higher plasma triiodothyronine recorded in the birds fed Curcuma longa in this present study depicts a better thermotolerance by the birds, suggesting the beneficial effect of the bioactive compounds of Curcuma longa . Consistent with our result [ 75 ], demonstrated chicks from hatching eggs sprayed with curcumin had higher plasma triiodothyronine.…”
Section: Discussionsupporting
confidence: 93%
“…The decrease in the MDA of birds of EG compared to the control birds in the present study suggests that curcumin, the bioactive compound in the Curcuma longa , was beneficial to the birds in attenuating the adverse effect of the thermal challenge to the birds were subjected. This observation is in harmony with the observation of [ 75 ], who demonstrated that chicks from the hatching eggs treated with curcumin had improved MDA levels. Additionally [ 76 , 77 ], reported that oxidant damage induced by thermal challenge was attenuated by curcumin.…”
Section: Discussionsupporting
confidence: 91%
“…Studies demonstrated that high temperatures are associated with low growth rates of nestling due to the altered foraging behavior of parents ( van de Ven et al, 2020 ). Likewise, during embryogenesis, daily exposure to 39°C during incubation retards organogenesis and affects chick performance in Dokki chickens ( Abuoghaba et al, 2021 ). Additionally, locomotor behavior in bobwhite quail hatchlings is also altered when exposed to a temperature of 38.1°C during early incubation, delaying bone growth, reducing body mass, and altering the structure of intertarsal joints ( Belnap et al, 2019 ).…”
Section: Parental Behavior In Precocial Species According To Breeding...mentioning
confidence: 99%
“…It should be noted that the treatment of hatching eggs with acids and oxidants has the purpose, in addition to exerting biocidal effects on harmful pathogens, of stimulating the metabolic rate of the developing embryo by improving transshell active and passive (diffusion) gas transport, first of all, oxygen, water vapor and carbon dioxide, which leads to significant increase in such an important indicator of incubation success as egg hatchability, which in turn increases the yield of healthy young birds (Breslavets et al, 2006). Both chemicals and physical factors have been successfully used for such stimulation (Wlazlo et al, 2020;Abuoghaba et al, 2021). Such modifications of commonly used poultry egg incubation technologies are used primarily for incubating eggs of bird breeds and crosses that have a naturally low hatchability rate, such as meat chicken breeds, or for farms that, due to force majeure, cannot ensure that poultry are kept in conditions for preserving hatching eggs which are in accordance with established standards.…”
Section: Introductionmentioning
confidence: 99%